Integration of SDGs into Gender-Equitable Spatial Planning in Lhokseumawe City - Nuribadah, Nuribadah; Iskandar, Hadi; Jafar, Sofyan; Nugraha, Satriya; Sari, Elidar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study examines the integration of Sustainable Development Goals (SDGs), particularly Goal 5 (Gender Equality) and Goal 11 (Sustainable Cities and Communities), into gender-responsive spatial planning in Lhokseumawe City, Indonesia. Despite national mandates to mainstream SDGs in regional planning, spatial policies at the local level remain largely gender-neutral and insufficiently address socio-ecological vulnerabilities. This research aims to analyze the extent of SDG integration in spatial planning policies and to identify gaps in their implementation. Using a qualitative socio-legal approach, data were collected through in-depth interviews, focus group discussions, and analysis of policy documents, including the Regional Spatial Planning (RTRW) and related regulations. The findings reveal that while normative frameworks for gender mainstreaming exist, their operationalization in spatial planning remains partial, fragmented, and weakly institutionalized. Key challenges include limited gender-responsive budgeting, insufficient technical guidelines, and weak cross-sectoral coordination. Additionally, environmental pressures, particularly in coastal and water catchment areas, exacerbate spatial inequalities affecting vulnerable groups, especially women. This study contributes to the literature by reconceptualizing spatial planning as a transformative instrument that integrates gender justice and ecological sustainability within the SDG framework. It proposes a policy-oriented framework that embeds gender indicators into spatial planning instruments, strengthens participatory governance, and aligns local planning practices with global sustainability targets. The findings highlight the urgency of shifting from gender-neutral to gender-responsive spatial governance to achieve inclusive and sustainable urban development.